Secure and efficient graduate employment: A consortium blockchain framework with InterPlanetary file system for privacy-preserving resume management and efficient talent-employer matching - Chin-Ling Chen; Kuang-Wei Zeng; Hsing-Chung Chen; Yong-Yuan Deng; Chin-Feng Lee; Der-Chen Huang; Ling-Chun Liu (PLoS ONE, 2025)
In recent years, the unemployment situation of teenagers has become increasingly serious, and many college students face the problem of unemployment upon graduation. Concurrently, Companies need more support in their talent acquisition processes, including high costs, security concerns, inefficiencies, and time-consuming sourcing procedures. Moreover, job applicants frequently confront risks associated with potentially compromising their personal information during the application process. Since blockchain technology has the characteristics of non-tampering, traceability, and non-repudiation, it has outstanding significance for solving the trust problem between organizations. Blockchain has emerged as a powerful tool for tackling talent acquisition campaigns. This study proposes a novel approach utilizing consortium chain technology in conjunction with the InterPlanetary File System (IPFS) to develop a decentralized talent recruitment system. This approach enables students, educational institutions, and potential employers to encrypt and upload data to the blockchain through consortium chain technology, with strict access controls requiring student authorization for resume data retrieval. The proposed system facilitates a symbiotic relationship between educational institutions and industry partners, allowing students to identify suitable employment opportunities while enabling companies to source candidates with requisite expertise efficiently. Finally, the system could meet the characteristic requirements of various blockchains, perform well in terms of communication cost, computing cost, throughput, and transaction delay in the blockchain, and contribute to solving talent recruitment.